Pengaruh Self-Compassion terhadap Perfectionistic Self-Presentation Remaja Akhir Pengguna TikTok - Ei Vidi Tiara; Siti Qodariah (Bandung Conference Series: Psychology Science, 2022)
Abstract. Social media is a lot of internet platforms to present themselves including TikTok with the majority of its users are late adolescene. Late adolescene at this age often present themselves on social media as a form of search and formation of self-identity and many late adolescene have a perfectionistic self-presentation attitude. Self-presentation on this variable includes the attitude of maladaptive perfectionism and these attitudes cause impacts such as stress, anxiety, to depression. Efforts to minimize the attitude of perfectionism is to increase self-compassion. This study aims to provide empirical data and determine the effect of these two variables on late teens using TikTok. The method used in this study is causality with a total of 406 subjects. The data analysis technique used is a simple regression test. The self-compassion measuring instrument uses the Self-Compassion Scale (SCS) from Neff and the perfectionistic self-presentation variable using the Perfectionistic Self-Presentation Scale (PSPS) from Hewitt. The results showed that the majority of late adolescene using TikTok in Bandung had a low level of self-compassion with a high perfectionistic self-presentation. The results of data processing show that self-compassion has a significant effect on perfectionistic self-presentation. The hypothesis t value is obtained. 0.000 > 0.05 (α) and the predicted result Y= 192750 – 0.619X with a negative direction from the result b = -1.011. The magnitude of the effect is 55.7%, meaning that the influence is at moderate level. Therefore, late adolescene are expected to increase self-compassion so that they can overcome the impact of perfectionistic self-presentation. Abstrak. Media sosial merupakan suatu platform internet yang banyak untuk menampilkan diri termasuk TikTok dengan mayoritas penggunanya adalah remaja akhir. Remaja akhir di usia ini banyak menampilkan dirinya di media sosial sebagai bentuk pencarian dan pembentukan identitas diri dan banyak remaja akhir yang memiliki sikap perfectionistic self-presentation. Presentasi diri pada variabel ini termasuk kepada sikap perfeksionisme yang maladaptif dan sikap tersebut menimbulkan dampak seperti stress, kecemasan, hingga depresi. Upaya untuk meminimalisir sikap perfeksionisme adalah dengan meningkatkan self-compassion. Penelitian ini bertujuan untuk memberikan data yang empiris dan mengetahui pengaruh kedua variabel pada remaja akhir pengguna TikTok. Metode yang digunakan dalam penelitian ini adalah kausalitas dengan total subjek adalah 406 orang. Teknik analisis data yang digunakan adalah uji regresi sederhana. Alat ukur self-compassion menggunakan Self-Compassion Scale (SCS) dari Neff dan variabel perfectionistic self-presentation menggunakan Perfectionistic Self-Presentation Scale (PSPS) dari Hewitt. Hasil penelitian menunjukan bahwa remaja akhir pengguna TikTok di Kota Bandung mayoritas memiliki tingkat self-compassion yang rendah dengan perfectionistic self-presentation yang tinggi. Hasil pengolahan data menunjukan bahwa self-compassion memiliki pengaruh yang signifikan terhadap perfectionistic self-presentation diperoleh nilai t Hipotesis. 0,000 > 0.05 (α) dan hasil prediksi Y= 192.750 – 0.619X dengan arah negatif dari hasil b = -1.011. Besaran pengaruhnya adalah 55.7% artinya pengaruh berada pada tingkat moderat. Oleh karena itu, bagi remaja akhir diharapkan dapat meningkatkan self-compassion sehingga dapat mengatasi dampak dari perfectionistic self-presentation.